Happiness and Work - Annabelle Krause (Institute for the Study of Labor (IZA), 2014)
The relationship between happiness and work is subject to an ever growing empirical literature in economics. The analyses are mostly based on large-scale survey data to measure subjective well-being. Whereas one large strand of research investigates the effect of job loss and becoming unemployed, another field of study focuses on the determinants of job satisfaction evolving around employment conditions, self-employment, and potential public sector satisfaction premiums. A smaller part of the literature investigates potential driving effects of happiness on labor market outcomes. This article will give an overview about the most significant subareas of research and the empirical literature in economics to date.
Keywords: I31; J28; J60; J64; 330; work; unemployment; self-employment; employment conditions; anticipation and adaptation effects; happiness; life satisfaction; job satisfaction; subjective well-being